PENGARUH KECAKAPAN PROFESIONAL, INDEPENDENSI DAN LAMA BEKERJA TERHADAP HASIL PEMERIKSAAN AUDITOR INTERNAL PADA INSPEKTORAT KABUPATEN/KOTA DI PROVINSI SULAWESI UTARA - Pasaribu, Sandi Hasudungan; Morasa, Jenny; Tangkuman, Steven (Universitas Sam Ratulangi, 2015)
In the area of financial management supervision entrusted by the Government Internal Supervisory Apparatus (APIP) as an internal auditor internal auditor eventually require attention to the quality of the examination done. Many factors affect the quality of audit reports become among other professional qualifications, independence and work experience. Professional qualifications and independence of the auditor is seen with regard to both th equality audit process and the audit results. Experienced auditors have advantages, including in terms of detecting errors, faults accurately understand, and look for the cause of the error. The purpose of this study was to determine the effect of professional competence, independence, and long working against the results of an internal auditor a the District / City in the province of North Sulawesi. Data collection methods used by the survey with a questionnaire containing a list of questions that are answered by the respondents selected that the internal auditor inspectorate. Data analysis techniques to test the hypothesis done using simple linear regression analysis and multiple linear regression were processed through SPSS ver 18.0. Based on the research results simultaneously (F test) showed that professionals kills variable (X1), Independence (X2), and longer working (X3) significantly affects the results of the internal auditor in thei nspectorate districts / citiesin North Sulawesi. As for theresults of research partially (t test) showed that the professional competence and independence of the variables significantly influence the results of the internal auditor in the inspectorate districts / cities in North Sulawesi, while for the old variable work does not affect the results of the auditor on the inspectorate district / city in North Sulawesi Province.